Rome has spoken a guide to forgotten papal statements, and how they have changed through the centuries (Crossroad, 1998)
Will the Roman Catholic Church ever change its position on women's ordination, contraception, clerical celibacy, or even infallibility itself? Is change possible, or are all teachings etched in stone? For some Catholics, the answer is in the old adage, "Rome has spoken, the case is closed." Yet history tells a different story. When Rome speaks, the debate often heats up. And the case is never closed